PENERAPAN ETIKA BISNIS ISLAM DALAM PENGELOLAAN UNIT USAHA PESANTREN AL-MASHDUQIAH TERHADAP KEMAJUAN BISNIS PESANTREN - Robiyatul Adawiyah; Jayanti Riska (IZZI: Jurnal Ekonomi Islam, 2023)
This study aims to analyze the implementation of Islamic business ethics in managing business units at Pesantren Al-Mashduqiah. Islamic business ethics emphasize values such as honesty, justice, trustworthiness, and responsibility as the foundation of economic activities. This research uses a descriptive qualitative method with a case study approach through interviews and direct observation. The results indicate that integrating Islamic business ethics with pesantren business management enhances consumer trust, strengthens business sustainability, and provides positive social impacts for the surrounding community. Beyond its educational role, Pesantren Al-Mashduqiah has succeeded in developing economic independence through professionally managed and sharia-compliant business units. These findings confirm that applying Islamic business ethics can serve as an effective strategy for developing pesantren business units oriented toward blessing and communal well-being.